O‘SMIRLARDA TASHABBUSKORLIK FAZILATLARINI SHAKLLANTIRISHNI O‘RGANISHGA YONDASHUVLAR TAHLILI - Mambetyarov, Sh. (SCIENCE and SOCIETY, 2024)
This article provides information about the need for citizens who can take initiative and take a new look at the current problems of modern society, and about some approaches to learning the formation of important human qualities such as mobility, competitiveness and initiative qualities in teenagers.